BUSINESS ETHICS AS A BASIS FOR DESIGNING THE VISION AND MISSION HOSPITALS: EMPIRICAL EVIDENCES FROM MUHAMMADIYAH HOSPITAL PONOROGO, INDONESIA - Anna Marina; Sentot Imam Wahjono (Journal of Economics, Business, and Accountancy Ventura, 2013)
This study aimed to identify business ethics practiced in hospital-based religious values as the basis for designing the vision and mission. Designing was done by discussing business ethics found in this research with the ethical and moral conceptsof Islam and Muhammadiyah. This research was conducted at Muhammadiyah hospital. This studyused a qualitative approach to the phenomenological analysis techniques to process data collected through in-depth interview, outside observation, and relevant documentation. In-depth interviews carried out ten times for eleven key informants. Focus Group Discussion held twice for twenty-one executive employees. Observation was done for eleven times over a period of six months, including observation and interviews with ten customers. Triangulation process is done by presenting the opinion of prominent figures in Muhammadiyah through his writing in several books onthe values of Muhammadiyah including basic ideological struggle of the Muhammadiyah founder KH Ahmad Dahlan. Similarly, the theory of Islamic Business Ethics findings are used to guide the Vision, Mission and then business ethics practiced by the management and employees of Muhammadiyah Hospital.